Polyacrylonitrile-based hydrogel and porous carbon material as well as preparation method and application of polyacrylonitrile-based hydrogel and porous carbon material
Through hydrothermal treatment and carbonization treatment, water is used as a solvent to solve the problems of organic solvent pollution and recycling difficulties, and porous carbon materials with high specific surface area are prepared, which improves the electrochemical performance of supercapacitors.
Patent Information
- Application Number
- CN202310746039.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-21
AI Technical Summary
There are problems of organic solvent contamination and recycling difficulties in the preparation of electrode materials of existing supercapacitors, and it is difficult to obtain uniform porous carbon materials during the carbonization process, resulting in poor quality reproducibility.
Using water as a solvent, hydrothermal treatment of biomass, graphene oxide and polyacrylonitrile and polyacrylonitrile was performed to prepare a polyacrylonitrile-based hydrogel, and porous carbon material was obtained by freeze-drying and carbonization treatment.
A green, non-toxic and simple preparation process is achieved, and a porous carbon material with uniform structure and high specific surface area is obtained, which improves the specific capacitance and energy density of the supercapacitor.
Smart Images

Figure CN119176954A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of preparation of polyacrylonitrile-based hydrogels, and in particular, to a polyacrylonitrile-based hydrogel and a porous carbon material, and a preparation method and application thereof. Background Art
[0002] Supercapacitors are considered to be one of the most promising energy storage devices due to their ultra-high power density and long cycle life. However, the energy density of commercial supercapacitors is still much lower than that of batteries, which greatly hinders their application. The electrode material of supercapacitors determines its performance. Electrode materials are mostly carbon-based materials, and carbon-based materials containing heteroatoms enhance surface wettability and conductivity. Therefore, incorporating nitrogen into the carbon matrix is crucial to enhancing capacitance performance. Polyacrylonitrile has become a precursor material for preparing carbon materials due to its comprehensive advantages of rich nitrogen elements, morphological adjustability and relatively high residual carbon rate; such as carbon fiber, carbon gel, etc.
[0003] At present, with polyacrylonitrile as the precursor, the research and development trends can be summarized into two aspects; the first is the research on novel polyacrylonitrile fiber forming process, such as using the plasticizer method to synthesize polyacrylonitrile copolymers in order to reduce the interaction between polyacrylonitrile monomers and thus reduce the melting point of the polymer, and using the melt spinning process or increasing the concentration of the spinning slurry in the dry-jet wet spinning process to achieve the purpose of improving the mechanical properties of the original fiber after fiber formation. The second is to study new varieties of polyacrylonitrile fibers. There are two main challenges in the research on polyacrylonitrile materials used as electrode materials in supercapacitors. The first is to obtain PAN-based porous carbon fibers by electrospinning. The main method used for preparing the spinning solution during electrospinning is to disperse polyacrylonitrile in an organic solvent (NN-dimethylacetamide, N-methylpyrrolidone or NN-dimethylformamide dimethyl sulfoxide) or an inorganic solvent (sodium thiocyanate, zinc chloride). The first method uses a large amount of organic solvents, which has the disadvantages of environmental pollution and time-consuming; the second method uses inorganic solvents, which has the disadvantages of difficult recovery, high material requirements for spinning equipment, and complex operation process. Another important challenge is that polyacrylonitrile usually needs to be pre-oxidized in air at 250°C to prevent melting during the subsequent high-temperature carbonization process. Such routes, methods and techniques are not only time-consuming but also require strict conditions. It is difficult to obtain a uniform mixture with the carbon precursor, which may lead to poor quality reproducibility of porous carbon prepared in different batches. Summary of the invention
[0004] The purpose of the present disclosure is to provide a polyacrylonitrile-based hydrogel and porous carbon material and a preparation method and application thereof. The preparation method is green and non-toxic, the preparation process is simple, the product structure is uniform and has a high specific surface area, and the problem of organic solvent pollution and difficulty in recovery is solved.
[0005] In order to achieve the above object, the present disclosure provides a method for preparing a polyacrylonitrile-based hydrogel in a first aspect, the method comprising the following steps:
[0006] S1: mixing polyacrylonitrile raw material, biomass, graphene oxide and water to obtain a mixed solution; and performing hydrothermal treatment on the mixed solution;
[0007] The biomass includes one or more of tannin compounds and lignin biomass.
[0008] Optionally, the tannin compound is selected from one or more of condensed tannin, phenolic tannin, tannic acid, and gallic acid; the lignin biomass is selected from one or more of lignin, alkali lignin, lignin sulfate, lignin sulfonate, enzymatic lignin, and organic solvent lignin; and the lignin sulfonate is selected from one or more of sodium lignin sulfonate and calcium lignin sulfonate.
[0009] Optionally, the polyacrylonitrile raw material is selected from one or more of polyacrylonitrile, acrylonitrile binary copolymer, and acrylonitrile ternary copolymer; the weight average molecular weight of the polyacrylonitrile raw material is 8000 to 250000;
[0010] The acrylonitrile binary copolymer is a copolymer of acrylonitrile monomer and a second monomer; the acrylonitrile terpolymer is a copolymer of acrylonitrile monomer, a second monomer and a third monomer;
[0011] The second monomer is one or more of methyl acrylate and methyl methacrylate; the third monomer is one or more of itaconic acid, sodium propylene sulfonate, sodium methpropylene sulfonate, sodium p-methacrylamide benzene sulfonate and methyl vinyl pyridine.
[0012] Optionally, the mass ratio of the biomass to the polyacrylonitrile raw material in S1 is 1:(0.5-5), the oxygen content of the graphene oxide is 10%-40%; the mixing time in S1 is 3-10 hours; the hydrothermal treatment conditions in S1 include a hydrothermal temperature of 120°C-180°C and a hydrothermal time of 20 hours-40 hours.
[0013] Optionally, step S1 includes the following steps:
[0014] S1-1, first mixing the polyacrylonitrile raw material with water, and obtaining a polyacrylonitrile water system after ultrasonic dispersion;
[0015] S1-2, mixing the biomass with water for a second time, and obtaining a biomass water system after ultrasonic dispersion;
[0016] S1-3, mixing graphene oxide with water for a third time, and dispersing by ultrasonication to obtain a graphene oxide system;
[0017] S1-4, performing a fourth mixing of the polyacrylonitrile water system, the biomass water system and the graphene oxide system obtained above to obtain the mixed solution;
[0018] The concentration of the graphene oxide system is 1 mg / mL to 6 mg / mL.
[0019] The second aspect of the present disclosure provides a polyacrylonitrile-based hydrogel prepared by the method described in the first aspect of the present disclosure.
[0020] A third aspect of the present disclosure provides a method for preparing a porous carbon material, the method comprising the following steps:
[0021] Freeze-drying the polyacrylonitrile-based hydrogel to obtain a water-based graphene polyacrylonitrile-based composite aerogel; and carbonizing the water-based graphene polyacrylonitrile-based composite aerogel;
[0022] The polyacrylonitrile-based hydrogel is the polyacrylonitrile-based hydrogel described in the second aspect of the present disclosure.
[0023] Optionally, the freeze-drying conditions include a freeze-drying temperature of -80 to -50°C and a time of 12 to 48 hours;
[0024] The carbonization treatment comprises treating the aqueous graphene polyacrylonitrile-based composite aerogel with an inorganic alkali solution under an inert atmosphere, the carbonization temperature being 600 to 800° C., and the carbonization time being 1 to 1.5 hours;
[0025] The inorganic base is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and sodium carbonate;
[0026] The mass ratio of the aqueous graphene polyacrylonitrile-based composite aerogel to the inorganic alkaline solution is 1:(1-5).
[0027] The fourth aspect of the present disclosure provides a porous carbon material prepared by the method described in the third aspect of the present disclosure, wherein the BET specific surface area of the porous carbon material is 300 to 900 m 2 / g; the total porosity is 45-70%; the mesopore volume accounts for 10-63% of the total pore volume; and the macropore volume accounts for 10-38% of the total pore volume.
[0028] The fifth aspect of the present disclosure provides an application of the porous carbon material described in the fourth aspect of the present disclosure in a supercapacitor.
[0029] Through the above technical scheme, the present invention uses water as a solvent, uses biomass materials to modify polyacrylonitrile, and adds graphene oxide dispersion liquid to obtain polyacrylonitrile-based hydrogel through a one-step hydrothermal method. The preparation method disclosed in the present invention is simple, the process is simple, green and non-toxic, and the cost is low. At the same time, the problems of organic solvent pollution and recycling difficulties are solved. The product structure has good uniformity, and the porous carbon material prepared by the polyacrylonitrile-based hydrogel is more conducive to the transmission of electrolytes in supercapacitors.
[0030] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0032] Figure 1 1 and 1. The photograph of the polyacrylonitrile-based hydrogel (a) and the photograph of the porous carbon material (b) in Example 1 of the present disclosure.
[0033] Figure 2 These are scanning electron microscope images (a and b) and a transmission electron microscope image (c) of the porous carbon material in Example 1 of the present disclosure. DETAILED DESCRIPTION
[0034] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0035] The first aspect of the present disclosure provides a method for preparing a polyacrylonitrile-based hydrogel, the method comprising the following steps:
[0036] S1: mixing polyacrylonitrile raw material, biomass, graphene oxide and water to obtain a mixed solution; and performing hydrothermal treatment on the mixed solution;
[0037] The biomass includes one or more of tannin compounds and lignin biomass.
[0038] The present invention prepares polyacrylonitrile-based hydrogel by using water as the solvent of polyacrylonitrile raw material, thereby overcoming the problems of organic solvent pollution and difficult recovery. The preparation method is simple, the process is easy, and it is green and non-toxic. At the same time, the polyacrylonitrile-based hydrogel is more conducive to the transmission of electrolytes in supercapacitors.
[0039] According to one embodiment of the present disclosure, the tannin compound is selected from one or more of condensed tannin, phenolic tannin, tannic acid, and gallic acid; the lignin biomass is selected from one or more of lignin, alkali lignin, lignin sulfate, lignin sulfonate, enzymatic lignin, and organic solvent lignin; the lignin sulfonate is selected from one or more of sodium lignin sulfonate and calcium lignin sulfonate. The above-mentioned embodiment mode is conducive to the high carbon yield and good atomic economy of the porous carbon material prepared from the polyacrylonitrile-based hydrogel, and further enables the supercapacitor to have a higher specific capacitance and energy density.
[0040] According to one embodiment of the present disclosure, the polyacrylonitrile raw material is selected from one or more of polyacrylonitrile, acrylonitrile binary copolymer, and acrylonitrile ternary copolymer; the weight average molecular weight of the polyacrylonitrile raw material is 8000-250000; the acrylonitrile binary copolymer is a copolymer of acrylonitrile monomer and a second monomer; the acrylonitrile ternary copolymer is a copolymer of acrylonitrile monomer, a second monomer, and a third monomer; the second monomer is one or more of methyl acrylate and methyl methacrylate; the third monomer is one or more of itaconic acid, sodium propylene sulfonate, sodium methpropylene sulfonate, sodium p-methacrylamide benzene sulfonate, and methyl vinyl pyridine. The above-mentioned embodiment mode is conducive to the high carbon yield and good atomic economy of the porous carbon material prepared from the polyacrylonitrile-based hydrogel, and further enables the supercapacitor to have a higher specific capacitance and energy density.
[0041] According to one embodiment of the present disclosure, the mass ratio of the biomass to the polyacrylonitrile raw material in S1 is 1: (0.5-5), preferably 1: (2-5); the oxygen content of the graphene oxide is 10%-40%, preferably 15%-30%. In the present disclosure, the oxygen content of the graphene oxide refers to the mass fraction of the oxygen element in the graphene oxide. The above-mentioned embodiment method is conducive to obtaining a porous carbon material with a larger BET specific surface area and a higher porosity, avoiding the collapse of the porous carbon material, and further making the supercapacitor have a higher specific capacitance and energy density.
[0042] According to an embodiment of the present disclosure, the mixing time in S1 is 3 to 10 hours, preferably 6 to 8 hours; the hydrothermal treatment conditions in S1 include a hydrothermal temperature of 120°C to 180°C, preferably 140°C to 160°C, and a hydrothermal time of 20h to 40h, preferably 28 to 30h. The above-mentioned embodiment method is conducive to obtaining a porous carbon material with a larger BET specific surface area and a higher porosity, and further enables the supercapacitor to have a higher specific capacitance and energy density.
[0043] According to an embodiment of the present disclosure, step S1 includes the following steps:
[0044] S1-1, first mixing the polyacrylonitrile raw material with water, and obtaining a polyacrylonitrile water system after ultrasonic dispersion;
[0045] S1-2, mixing the biomass with water for a second time, and obtaining a biomass water system after ultrasonic dispersion;
[0046] S1-3, mixing graphene oxide with water for a third time, and dispersing by ultrasonication to obtain a graphene oxide system;
[0047] S1-4, performing a fourth mixing of the polyacrylonitrile water system, the biomass water system and the graphene oxide system obtained above to obtain the mixed solution;
[0048] The concentration of the graphene oxide system is 1 mg / mL to 6 mg / mL.
[0049] The second aspect of the present disclosure provides a polyacrylonitrile-based hydrogel prepared by the method described in the first aspect of the present disclosure.
[0050] A third aspect of the present disclosure provides a method for preparing a porous carbon material, the method comprising the following steps:
[0051] Freeze-drying the polyacrylonitrile-based hydrogel to obtain a water-based graphene polyacrylonitrile-based composite aerogel; and carbonizing the water-based graphene polyacrylonitrile-based composite aerogel;
[0052] The polyacrylonitrile-based hydrogel is the polyacrylonitrile-based hydrogel described in the second aspect of the present disclosure.
[0053] According to one embodiment of the present disclosure, the freeze-drying conditions include a freeze-drying temperature of -80 to -50°C, preferably -45 to -60°C; and a time of 12 to 48 hours, preferably 24 to 38 hours.
[0054] According to one embodiment of the present disclosure, the carbonization treatment includes subjecting the aqueous graphene polyacrylonitrile-based composite aerogel to an inorganic alkali solution under an inert atmosphere, the carbonization temperature is 600-800°C, and the carbonization time is 1-1.5h; preferably, the carbonization temperature is 700-800°C. In a further embodiment, the carbonization treatment includes subjecting the aqueous graphene polyacrylonitrile-based composite aerogel to an inorganic alkali solution in a molten state under the protection of an inert atmosphere. The above-mentioned embodiment mode does not require a soft template or a hard template to obtain a porous carbon material, the method is simple, and it is also conducive to obtaining a porous carbon material with a larger BET specific surface area and a higher porosity, which further enables the supercapacitor to have a higher specific capacitance and energy density.
[0055] According to an embodiment of the present disclosure, the inorganic base is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and sodium carbonate; the mass ratio of the aqueous graphene polyacrylonitrile-based composite aerogel to the inorganic base solution is 1: (1-5), preferably 1: (2-4); the inert atmosphere includes one or more of nitrogen, helium and argon. The above-mentioned embodiment method is conducive to obtaining a porous carbon material with a larger BET specific surface area and a higher porosity, which further enables the supercapacitor to have a higher specific capacitance and energy density.
[0056] The fourth aspect of the present disclosure provides a porous carbon material prepared by the method described in the third aspect of the present disclosure, wherein the BET specific surface area of the porous carbon material is 300 to 900 m 2 / g; the total porosity is 45-70%; the proportion of mesopore volume in the total pore volume is 10-63%; the proportion of macropore volume in the total pore volume is 10-38%; preferably, the BET specific surface area of the porous carbon material is 500-900m 2 / g; the total porosity is 60-70%; the mesopore volume accounts for 23-63% of the total pore volume; and the macropore volume accounts for 10-30% of the total pore volume.
[0057] The fifth aspect of the present disclosure provides an application of the porous carbon material described in the fourth aspect of the present disclosure in a supercapacitor.
[0058] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0059] The polyacrylonitrile raw material used in the examples was purchased from Shanghai Petrochemical Co., Ltd.; tannic acid was purchased from MacLean Reagent Company; calcium lignin sulfonate and sodium lignin sulfonate were purchased from Hefei BASF Biotechnology Co., Ltd. Unless otherwise specified, the remaining reagents were commercially available.
[0060] The BET test was performed on an instrument model JW-BK200C.
[0061] SEM was performed on a JSK-6480A scanning electron microscope.
[0062] TEM was performed on a transmission electron microscope (Bioscope system).
[0063] The electrochemical workstation was operated on a CHI600E instrument.
[0064] The blue electric system was tested on an instrument model CT2001A, and the specific test method was a cyclic stability test.
[0065] The graphene oxide used in the examples was prepared by referring to the method of the doctoral dissertation "Preparation and Performance Study of Graphene-based Cobalt Oxide (Hydroxide) Composite Materials" by Lin Bao, to obtain graphene oxide with oxygen contents of 5%, 15% and 30%.
[0066] Example 1
[0067] (1) Add 2 g of polyacrylonitrile (molecular weight 80,000) into 5 ml of deionized water, stir, and ultrasonically disperse for 3 h to obtain a polyacrylonitrile water system;
[0068] (2) adding 4 g of calcium lignin sulfonate to 5 ml of deionized water, stirring, and ultrasonically dispersing for 3 h to obtain a biomass water system;
[0069] (3) adding 10 mL of 4 mg / mL graphene oxide with an oxygen content of 15% to 10 mL of deionized water, stirring, and ultrasonically dispersing for 3 h to obtain a graphene oxide system;
[0070] (4) mixing the polyacrylonitrile water system, the biomass water system and the graphene oxide system, and stirring for 5 hours to obtain a uniform mixed solution; the mass ratio of the added biomass to the polyacrylonitrile raw material is 1:2;
[0071] (5) transferring the mixed solution to a high pressure reactor for hydrothermal treatment at a temperature of 150° C. for 30 h to obtain a polyacrylonitrile-based hydrogel;
[0072] (6) freeze-drying the obtained polyacrylonitrile-based hydrogel at a temperature of -60°C for 36 hours to obtain a water-based graphene polyacrylonitrile-based composite aerogel;
[0073] (7) The aqueous graphene polyacrylonitrile-based composite aerogel was mixed with a 6 mol / L KOH solution in a mass ratio of 1:1, dried at 80 °C for 8 h, and then transferred to a tubular furnace and carbonized at 700 °C for 1 h under the protection of inert gas nitrogen to obtain a porous carbon material.
[0074] Example 2
[0075] (1) Add 2 g of polyacrylonitrile (molecular weight 250,000) into 5 ml of deionized water, stir, and ultrasonically disperse for 3 h to obtain a polyacrylonitrile water system;
[0076] (2) Add 6 g of tannic acid into 5 ml of deionized water, stir, and ultrasonically disperse for 3 h to obtain a biomass water system;
[0077] (3) adding 10 mL of 5 mg / mL graphene oxide with an oxygen content of 30% to 10 mL of deionized water, stirring, and ultrasonically dispersing for 3 h to obtain a graphene oxide system;
[0078] (4) mixing the polyacrylonitrile water system, the biomass water system and the graphene oxide system, and stirring for 7 hours to obtain a uniform mixed solution; the mass ratio of the added biomass to the polyacrylonitrile raw material and the graphene oxide is 1:3;
[0079] (5) transferring the mixed solution to a high pressure reactor for hydrothermal treatment at a temperature of 120° C. for 25 h to obtain a polyacrylonitrile-based hydrogel;
[0080] (6) freeze-drying the obtained polyacrylonitrile-based hydrogel at a temperature of -80°C for 24 hours to obtain a water-based graphene polyacrylonitrile-based composite aerogel;
[0081] (7) The aqueous graphene polyacrylonitrile-based composite aerogel was mixed with a 5 mol / L KOH solution in a mass ratio of 1:3, dried at 80 °C for 8 h, and then transferred to a tubular furnace and carbonized at 800 °C for 1.2 h under the protection of inert gas nitrogen to obtain a porous carbon material.
[0082] Example 3
[0083] The method of this embodiment is the same as that of embodiment 1, except that 4 g of polyacrylonitrile is weighed in (1), 1 g of biomass is weighed in (2), and the mass ratio of biomass to polyacrylonitrile raw materials in (4) is 1:0.25.
[0084] Comparative Example 1
[0085] (1) Add 2 g of polyacrylonitrile (molecular weight 80,000) into 5 ml of deionized water, stir, and ultrasonically disperse for 3 h to obtain a polyacrylonitrile water system;
[0086] (2) Add 4 g of sodium lignin sulfonate to 5 ml of deionized water, stir, and ultrasonically disperse for 3 h to obtain a biomass water system;
[0087] (3) mixing the polyacrylonitrile water system and the biomass water system, stirring for 5 hours, and obtaining a uniform mixed solution; the mass ratio of the added biomass to the polyacrylonitrile raw material is 1:2;
[0088] (4) transferring the mixed solution to a high pressure reactor for hydrothermal treatment at a temperature of 150° C. for 30 h to obtain a polyacrylonitrile-based hydrogel;
[0089] (5) freeze-drying the obtained polyacrylonitrile-based hydrogel at a temperature of -60°C for 36 hours to obtain a water-based polyacrylonitrile-based composite aerogel;
[0090] (6) The aqueous polyacrylonitrile-based composite aerogel was mixed with a 6 mol / L KOH solution in a mass ratio of 1:1, dried at 80 °C for 8 h, and then transferred to a tubular furnace and carbonized at 700 °C for 1 h under the protection of inert gas nitrogen to obtain a porous carbon material.
[0091] Test Example 1
[0092] The porous carbon materials obtained in Examples 1 to 3 and Comparative Example 1 were subjected to BET tests. The test results are shown in Table 1.
[0093] Table 1
[0094]
[0095]
[0096] According to the data in Table 1, the porous carbon material prepared by the method of the present invention has a large BET specific surface area, a high total porosity, and a high proportion of mesopore volume in the total pore volume, indicating that the porous carbon material obtained by the method of the present invention has more mesopores.
[0097] Test Example 2
[0098] The porous carbon materials obtained in Examples 1 to 3 and Comparative Example 1 were tested for electrochemical performance. The specific method was as follows: the porous carbon materials obtained in Examples 1 to 3 and Comparative Example 1 were mixed with a conductive agent, acetylene black, and a binder, PVDF (PVDF was a 60 wt.% suspension in NMP) at a mass ratio of 8:1:1, and coated on a 1 cm 2 The electrodes as current collectors were pressed onto square nickel foam. They were then dried at 80 °C for 12 h. The area of each working electrode was 0.5 cm 2 , mass loading was 1.5-4 mg. Both three-electrode and two-electrode tests were performed on a CHI 660E electrochemical workstation. CV tests were performed in a potential window range of -1.2 V to 0.6 V by changing the scan rate. GCD tests were performed at current densities of 0.5 to 20 A. -1 Place the electrode in the blue electric system test.
[0099] In the three-electrode test, the platinum electrode is used as the counter electrode and the Hg / HgO electrode is used as the reference electrode. The specific capacitance is calculated by the formula C = IΔt / (m*ΔV); where C is the specific capacitance of the electrode (Fg -1), Δt is the discharge time of the GCD curve (s); ΔV is the voltage window range obtained by the test (V), I is the response current (A), and ν is the scan rate used in the test (Vs -1 ), m is the mass of active material loaded on the working electrode (g).
[0100] The two symmetrical electrode system uses carbon material coated on nickel foam as the positive and negative electrodes, separated by a water-based diaphragm dedicated to supercapacitors. The battery shell uses 2016 and 2023 button-type motor shells. After assembly at room temperature, the tablet press is packaged and compacted and tested, and the cycle stability test is carried out in the blue battery test system. The power density P is calculated according to the formula P = E * 3600 / Δt, and the energy density E is calculated by the formula E = C * ΔV 2 / (2*3.6) calculation: Where P is the power density (Wkg -1 ), E is the energy density (Wh kg -1 ), ΔV (V) and Δt (s) are the GCD voltage window and discharge time of the two-electrode test. The test results are shown in Table 2.
[0101] Table 2
[0102]
[0103] According to the data in Table 2, the porous carbon material prepared by the method of the present disclosure has higher specific capacitance and energy density when made into a supercapacitor. By comparing Example 3 with Example 1, it can be seen that within the mass ratio range of the biomass to polyacrylonitrile raw material disclosed in the present disclosure, the porous carbon material has higher specific capacitance and energy density when made into a supercapacitor.
[0104] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0105] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0106] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing polyacrylonitrile-based hydrogel, characterized in that: The method comprises the following steps: S1: mixing polyacrylonitrile raw material, biomass, graphene oxide and water to obtain a mixed solution; and performing hydrothermal treatment on the mixed solution; The biomass includes one or more of tannin compounds and lignin biomass.
2. The method according to claim 1, wherein: The tannin compound is selected from one or more of condensed tannin, phenolic tannin, tannic acid, and gallic acid; the lignin biomass is selected from one or more of lignin, alkali lignin, lignin sulfate, lignin sulfonate, enzymatic lignin, and organic solvent lignin; and the lignin sulfonate is selected from one or more of sodium lignin sulfonate and calcium lignin sulfonate.
3. The method according to claim 1, wherein: The polyacrylonitrile raw material is selected from one or more of polyacrylonitrile, acrylonitrile binary copolymer and acrylonitrile ternary copolymer; the weight average molecular weight of the polyacrylonitrile raw material is 8000 to 250000; The acrylonitrile binary copolymer is a copolymer of acrylonitrile monomer and a second monomer; the acrylonitrile terpolymer is a copolymer of acrylonitrile monomer, a second monomer and a third monomer; The second monomer is one or more of methyl acrylate and methyl methacrylate; the third monomer is one or more of itaconic acid, sodium propylene sulfonate, sodium methpropylene sulfonate, sodium p-methacrylamide benzene sulfonate and methyl vinyl pyridine.
4. The method according to claim 1, wherein: The mass ratio of the biomass to the polyacrylonitrile raw material and the graphene oxide in S1 is 1:(0.5-5), and the oxygen content of the graphene oxide is 10%-40%; The mixing time in S1 is 3 to 10 hours; the hydrothermal treatment conditions in S1 include a hydrothermal temperature of 120° C. to 180° C. and a hydrothermal time of 20 to 40 hours.
5. The method according to claim 1, wherein: Step S1 includes the following steps: S1-1, first mixing the polyacrylonitrile raw material with water, and obtaining a polyacrylonitrile water system after ultrasonic dispersion; S1-2, mixing the biomass with water for a second time, and obtaining a biomass water system after ultrasonic dispersion; S1-3, mixing graphene oxide with water for a third time, and dispersing by ultrasonication to obtain a graphene oxide system; S1-4, performing a fourth mixing of the polyacrylonitrile water system, the biomass water system and the graphene oxide system obtained above to obtain the mixed solution; The concentration of the graphene oxide system is 1 mg / mL to 6 mg / mL.
6. The polyacrylonitrile-based hydrogel prepared by the method according to any one of claims 1 to 5.
7. A method for preparing a porous carbon material, characterized in that: The method comprises the following steps: Freeze-drying the polyacrylonitrile-based hydrogel to obtain a water-based graphene polyacrylonitrile-based composite aerogel; and carbonizing the water-based graphene polyacrylonitrile-based composite aerogel; The polyacrylonitrile-based hydrogel is the polyacrylonitrile-based hydrogel described in claim 6.
8. The method according to claim 7, wherein: The freeze-drying conditions include a freeze-drying temperature of -80 to -50°C and a time of 12 to 48 hours; The carbonization treatment comprises treating the aqueous graphene polyacrylonitrile-based composite aerogel with an inorganic alkali solution under an inert atmosphere, the carbonization temperature being 600 to 800° C., and the carbonization time being 1 to 1.5 hours; The inorganic base is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and sodium carbonate; The mass ratio of the aqueous graphene polyacrylonitrile-based composite aerogel to the inorganic alkali solution is 1:(1-5); the concentration of the inorganic alkali solution is 1-6 mol / L.
9. The porous carbon material prepared by the method according to any one of claims 7 or 8, characterized in that: The BET specific surface area of the porous carbon material is 300 to 900 m 2 / g; the total porosity is 45-70%; the mesopore volume accounts for 10-63% of the total pore volume; and the macropore volume accounts for 10-38% of the total pore volume.
10. Use of the porous carbon material according to claim 9 in a supercapacitor.
Citation Information
Patent Citations
Flexible carbon fiber and preparation method thereof
CN106012110A
Biomass auxiliary preparation method and application of nitrogen doped graphene
CN106395803A
Method for preparing hydrogel flexible electrode by tannic acid-modified graphene oxide
CN108493002A
Method for preparing polyamidoxime / graphene nanobelt composite aerogel and method for separating and enriching uranium
CN111484644A
Preparation method and application of graphene / polyacrylonitrile nanofiber composite aerogel
CN111777791A
